Chronotype as a predictor of athletic performance in youth with mild intellectual disabilities - Kurtoğlu, Ahmet; Eken, Özgür; Türkmen, Musa; Çar, Bekir; Setiawan, Edi; Yermakhanov, Baglan; Alotaibi, Madawi H.; Elkholi, Safaa M. (Frontiers in Physiology, 2024)
Aim: This study aimed to explore the influence of circadian rhythms on athletic performance in individuals with mild intellectual disabilities (ID), with a specific focus on elucidating the association between chronotype and various performance metrics.Methods: The study was a cross-sectional study consisting of 30 male participants aged between 11 and 19 years and diagnosed with mild ID. The chronotypes of all participants were assessed using the Childhood Chronotype Questionnaire (CCQ). Performance assessments were divided into three groups. Group A tests [sit and reach, medicine ball throw (MBT), plank], group B tests [handgrip strength (HGS), standing long jump (SLJ), 20-metre sprint (20m S)] and group C tests [vertical jump (VJ), hanging with bent arm (HBA), Illinois agility test) in order to ensure adequate rest periods between tests and not to affect the results. These group tests were performed 48 hours apart, between 09:00-10:00 and 17:00-18:00, after a dynamic warm-up session.Results: Significant variations were observed in the sit-and-reach test (t=-4.154, d=-0.75, p<.001), HGS (t=-2.484, d=-0.45, p=.019), SLJ (t=-2.117, d=-0.38, p=.043), VJ (t=-5.004, d=-0.91, p<.001), and plank duration (t=-4.653, d=-0.84, p<.001). Evening performances showed improvement in MBT, HBA, 20mS, and the Illinois agility test, although these differences were not statistically significant (p>.05). Notably, positive correlations were identified between participants' chronotypes and their performance in HBA (morning/evening; r=.693, p=.026; r=.656, p=.039, respectively) and the plank (evening; r=.717, p=.020), with negative correlations noted in the 20mS (morning/evening; r=-.703, p=.023; r=-.710, p=.021, respectively). Conclusion:The findings suggest that individuals with mild ID exhibit enhanced athletic performance during evening hours. These insights underscore the importance of considering chronotype in tailoring exercise interventions for this population to optimize outcomes.